World Outlook and State of Food and Agriculture 1950 - Food; Agriculture Organization of the United Nations (United Nations, 1950)
In line with recommendations of the Fifth Session of the FAO Conference, this report brings together information on the general economic outlook; the outlook for individual farm, forestry, and fisheries commodities; the changing patterns of world trade; the changes in international investment; and the general state of food and agriculture.